Two Suns of the Southwest : Lyndon Johnson, Barry Goldwater, and the 1964 Battle between Liberalism and Conservatism - Young, Nancy Beck (Book collections on Project MUSE., 2019)
"Two Suns of the Southwest: Lyndon Johnson, Barry Goldwater, and the 1964 Battle Between Liberalism and Conservatism explores the 1964 presidential election and its legacy for modern American politics. The contest was simultaneously a showdown between liberalism and conservatism and between Lyndon B. Johnson and Barry Goldwater. Two more unlikely messengers could not be envisioned. Johnson's liberalism was suspect among east coast liberals while Goldwater's conservatism was far to the right of what had been normal in previous decades. Both suns of the Old West, they advocated distinctly different versions of what the southwest and thus the country could be if it but orbited their worldview. One looked nostalgically backward and the other boldly forward. The election of 1964 has in the decades since come to be seen as a definitional contest whereby Americans deliberated between two distinctly different visions for the future. To provide an additional twist, the losing candidate's vision has become much more central to American politics while the winning candidate's vision has grown stale"--